2011
DOI: 10.1007/s11856-011-0157-7
|View full text |Cite
|
Sign up to set email alerts
|

Multilinear commutators in residually finite groups

Abstract: Abstract. The following result is proved. Let w be a multilinear commutator and n a positive integer. Suppose that G is a residually finite group in which every product of at most 896 w-values has order dividing n. Then the verbal subgroup w(G) is locally finite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…However, the next result gives a sufficient condition for a quotient to be locally graded. Shumyatsky in [15] has showed that if w is a multilinear commutator and G is a residually finite group in which for any product of at most 896 w-values x there exists a positive integer q = q(x) dividing a fixed positive integer m such that x q = 1, then the verbal subgroup w(G) is locally finite. Next, we extend this result to the class of locally graded groups.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the next result gives a sufficient condition for a quotient to be locally graded. Shumyatsky in [15] has showed that if w is a multilinear commutator and G is a residually finite group in which for any product of at most 896 w-values x there exists a positive integer q = q(x) dividing a fixed positive integer m such that x q = 1, then the verbal subgroup w(G) is locally finite. Next, we extend this result to the class of locally graded groups.…”
Section: Preliminariesmentioning
confidence: 99%
“…We need the following result, due to Shumyatsky [15]. In particular, every w-value in G has finite order.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The problematic Lemma 2.5 of [13] was later used in [14] and [4]. In [14] it was used in the proof of the following result ( [14,Proposition 3.4…”
Section: Correcting An Error In An Earlier Papermentioning
confidence: 99%